Good’s Syndrome: Time to Move on From Reviewing the Past - Kabir, Aunonna; Alizadehfar, Reza; Tsoukas, Christos M. (Frontiers in Immunology, 2022)
For seven decades, the pathophysiology of Good’s syndrome (GS) has remained a mystery, with few attempts to solve it. Initially described as an association between hypogammaglobulinemia and thymoma, controversy exists whether this is a unique disease, or a subgroup of Common Variable Immune Deficiency (CVID). Recently, some distinguishing aspects of both syndromes have come to light reflecting fundamental differences in their underlying pathophysiology. GS and CVID differ in demographic features and immune phenotype. GS is found almost exclusively in adults and is characterized by a significantly reduced or absence of peripheral B cells. In CVID, which also occurs in children, most patients have normal or slightly reduced peripheral B cells, with a distinguishing feature of low memory B cells. Similarly, differences in T cell dysregulation and manifestations of hematologic cytopenias may further distinguish GS from CVID. Knowledge of the clinical phenotype of this rare adult immune deficiency stems from individual case reports, retrospective, and cross-sectional data on a few cohorts with a limited number of well characterized patients. The understanding of pathophysiology in GS is hampered by the incomplete and inconsistent reporting of clinical and laboratory data, with a limited knowledge of its natural history. In this mini review, we discuss current state of the art data and identify research gaps. In order to resolve controversies and fill in knowledge gaps, we propose a coordinated paradigm shift from incidence reporting to robust investigative studies, addressing mechanisms of disease. We hope this novel approach sets a clear direction to solve the current controversies.